No doctoral studies without hurdles: A review on pathways to prevent dropouts - Shadreck Muchaku; Marizvikuru Mwale; Grey Magaiza; Malose Moses Tjale (Interdisciplinary Journal of Education Research, 2024)
Traditionally, doctoral studies take at least three to six years of full-time study, depending on the country and institution. However, the number of doctoral students who complete their studies in the prescribed time does not meet the expectations of the scientific community. Many students who enrol in a doctoral programme either drop out or do not complete it within the expected time frame. The literature is replete with evidence of the challenges faced by early career researchers, but there is still little reported on how to bridge the existing and perceived barriers that continue to undermine doctoral study retention. These and other obstacles must be addressed and combated by questioning the root causes of students dropping out of their studies. Thus, this study sought to suggest pathways to overcome these and other obstacles by providing a coherent overview of what we need to do and how. The methodology used included a thorough review of international accredited peer reviewed articles extracted from the SCOPUS multidisciplinary database. A total of 24 articles relevant to the topic were thus selected. The key finding of this initiative is that doctoral students face wide-ranging financial, academic, and social challenges that need to be addressed innovatively to improve the timely realisation of the successful completion of their studies.